EVALUASI KONTRIBUSI KESELAMATAN DAN KESEHATAN KERJA DALAM MENDORONG PRODUKTIVITAS KARYAWAN DI LINGKUNGAN PERKEBUNAN SAWIT PT. “ABC” - Mardan, Jhonni Ardan (Komunitas Manajemen Kompetitif, 2025)
The purpose of this study was to determine the effect of occupational safety and health on the productivity of employees of PT. ABC. To achieve these objectives, research was conducted using a sample of 63 people, using the census method. The method of data analysis uses simple linear regression. Then it can be concluded that Ho is rejected and Ha is accepted, which means that occupational health and safety has a significant effect on the productivity of employees of PT. ABC. Based on the calculation results to see how much the percentage of independent variables contributed to the dependent variablethen the percentage of contribution or contribution of independent variables to the dependent variable. The recommendation that can be submitted is that it is expected that occupational health and safety for employees must be tightened again as prohibited from making irregularities on dangerous goods, so employees maintain health and safety at work